Case Report: A comprehensive case study on aggressive high-grade urothelial carcinoma of bladder that transforms into enteric-type adenocarcinoma along with an integrated treatment approach - Rahul, Neha; Jules, Manishimwe; Weerarathna, Induni Nayodhara; Luharia, Anurag; Dube, Prashik (Frontiers in Radiology, 2025)
Bladder cancer is a malignant tumour with a high morbidity and mortality rate in the world. Moreover, it is the most prevalent as well as commonly diagnosed in older individuals, with a median age of 73 years, and it has been reported that the most frequently seen histological type of bladder cancer was urothelial carcinoma. We present a unique case of a 44-year-old female with enteric-type adenocarcinoma, a rare and aggressive bladder cancer. Her symptoms included frequent micturition (Urination) and hematuria (blood in urine), at which point she was diagnosed with High-grade urothelial carcinoma. The malignancy worsened despite cycles of treatment requiring extensive surgery. After further tests, it was found that she had urothelial carcinoma with features of intestinal tissue (tissue of the intestine) and that the disease had infiltrated into nearby blood vessels and nerves. Radiation therapy was recommended to decrease the risk of local recurrence after surgery. The challenges in treating such a patient and the positive aspects this approach can give are highlighted in a case report.